COMPETENCY BASED CURRICULUM IMPLEMENTATION AND PERFORMANCE IN MATHEMATICS AMONG GRADE FOUR PRIMARY SCHOOL PUPILS IN MACHAKOS SUB-COUNTY, KENYA - DANIEL MUMO NZUKI (Machakos University Press, 2025)
Despite the introduction of CBC aimed at improving practical skills and competences, persistent problems remain, including inadequate teacher training, limited resources and large class sizes. The research was guided by four objectives; to establish how teachers’ of Mathematics induction on CBC affects performance in Mathematics, to determine how adoption of new CBC lesson planning strategies by Mathematics teachers affects performance, to establish how Mathematics teachers’ adoption of new CBC assessment strategies affects performance, to establish how the supervision of the implementation of CBC affects performance in Mathematics among Grade 4 pupils. The study adopted the constructivist theory of learning. It further employed a mixed methods research design. The target population included all the primary schools, head teachers, grade 4 mathematics teachers and grade four pupils from all public and private primary schools from Machakos Sub-County. This study adopted the multi-stage sampling technique: stratified random sampling was used to select 19 public primary and 5 private primary schools in Machakos Sub-county; in each of the 24 sampled schools, one grade 4 stream was randomly sampled; one head teacher was purposively sampled and the one grade 4 mathematics teacher for the sampled stream was purposively sampled. The sample comprised of 19 public primary and 5 private primary schools, 24 head teachers, 24 teachers of mathematics and 337 grade 4 pupils. The reliability of the instruments was established using the Cronbach Alpha attaining 0.82. The quantitative data was analyzed using the SPSS Version 28, while qualitative data was analyzed using Thematic Analysis. The results of the study demonstrated that; efficient implementation of the CBC strategies greatly enhanced performance in Mathematics among Grade 4 pupils. In this regard, teachers were adequately inducted on CBC, grade 4 mathematics teachers’ adopted new lesson planning and schemes of work under CBC, adopted various assessment methods as spelt out in the new CBC and teacher’s supervision on the implementation of the CBC was very crucial. The study recommends that the Ministry of Education should create comprehensive and ongoing professional development programs that focus not only on the theoretical aspects of the Competency-Based Curriculum (CBC) but also on practical application in the classroom ,ensure that schools have sufficient teaching resources and materials that are aligned with the CBC framework, implement robust accountability systems for teachers to ensure consistent participation in professional development programs and adherence to CBC standards and encourage schools to actively involve parents and communities in the learning process, especially in mathematics education.